Spousal Presence Modulates Salivary α-Amylase Responses to Infant Cry in Mothers With High Attachment Insecurity. (3rd April 2019) - Hiraoka, Daiki; Miyasaka, Mami; Nomura, Michio
SYNOPSIS: Objective : Infant cry, a major stressor for caregivers, is one of the leading triggers of child abuse. The present study examined the effects of spousal support, spousal presence, and the possible moderating effect of attachment insecurity on individuals' subjective and physiological responses to infant cry. Design: Thirty-one healthy mothers ( M age = 36 years) and their spouses participated in an infant crying paradigm, where mothers were tasked to listen to infant cries under three conditions: (1) alone, (2) in the same room as partner, without physical contact, and (3) in the same room as partner, with hand-holding. Attachment was determined using the Experiences in Close Relationship Questionnaire, and physiological response was ascertained from concentration of salivary α-amylase (sAA). After each cry sound, sAA level and subjective responses to infant cry were assessed. Results: Multilevel regression analyses revealed that trait attachment-anxiety moderated the effect of spousal presence on sAA. Specifically, mothers with high attachment-anxiety showed reduced sAA when their spouse was present, which indicates that spousal support is effective for mothers with high attachment-anxiety. Conclusions: Findings from this study translate to promising clinical applications for the management of parenting stress from infant cry.